Aqueous Symmetric Supercapacitors with Carbon Nanorod Electrodes and Water‐in‐Salt Electrolyte. Issue 2 (28th November 2018) - Xiao, Dewei; Wu, Qihui; Liu, Xiaolei; Dou, Qingyun; Liu, Lingyang; Yang, Bingjun; Yu, Haiyun
Abstract: Although safe and low‐cost aqueous supercapacitors have gained great attention, their narrow operation voltage significantly limits their widespread applications. Here, we demonstrate a high‐voltage and high‐capacitance aqueous symmetric supercapacitor by using polyaniline‐derived carbon nanorods as the electrodes and a highly concentrated water‐in‐salt [lithium bis(trifluoromethane sulfonyl) imide dissolved in water] electrolyte. The resultant supercapacitor is able to work with a wide operation voltage window of 2.2 V and shows a high specific capacitance of 44 F g −1 at a current density of 1 A g −1 . Moreover, it exhibits a superior rate capability (73 % capacitance retention upon increasing current density from 1 to 10 A g −1 ). Consequently, the favorable combination of high specific capacitance, wide operation voltage window, and excellent rate capability enable the device to have comparable energy and power densities to those of commercial non‐aqueous supercapacitors. Abstract : Optimizing aqueous supercapacitors : A new aqueous supercapacitor is constructed by utilizing polyaniline‐derived carbon nanorod (PDCN) electrodes and 21 m water‐in‐salt electrolyte, which presents high energy and high power densities, benefiting from the synergistic effect.